Competing and Conflicting Interests in the Care of Critically ill Patients - Turnbull, Alison E. (Intensive Care Med, 2018)
Medical professionals are expected to prioritize patient interests and most patients trust physicians to act in their best interest. But a single patient is never a physician’s sole concern. The competing interests of other patients, clinicians, family members, hospital administrators, regulators, insurers, and trainees are omnipresent. While prioritizing patient interests is always a struggle, it is especially challenging and important in the ICU setting where most patients lack the ability to advocate for themselves or seek alternative sources of care. This review explores factors that increase the risk, or the perception, that an ICU physician will reason, recommend, or act in a way that is not in their patient’s best interest, and discusses steps that could help minimize the impact of these factors on patient care.